DEVELOPMENT AND PARAMETER ESTIMATION OF A COMPACT ELECTRONIC WEDGE BRAKE TEST RIG USING GREY BOX SYSTEM IDENTIFICATION - Che Hasan, M. H.; Hassan, M. K.; Ahmad, F.; Marhaban, M. H.; Haris, S. I. (Journal of Mechanical Engineering and Technology (JMET), 2023)
This article presented the development of a compact electronic wedge brake (EWB) based brake test rig and the estimation of model parameters through system identification (SI). The EWB test rig was huge and complex, leading to high costs and time consumption. Additionally, the EWB parameters estimation was limitedly discussed. Thus, a compact test rig was developed to produce up to 300N of braking force, which was acceptable to demonstrate the effectiveness of the model and EWB performance. Two separate transfer function models for the motor and EWB mechanism were proposed. The parameter estimation was made using the grey box approach, which combined physical modelling and SI. The complete physical parameters value via two separated SI was successfully obtained. The brake responses were analysed by comparing the simulation and experiment under rapid control prototyping (RCP). The average percentage of root mean square error (RMSE) value between the simulation and experiment was less than 6.23%. The test rig configuration and proposed model guarantees were useful in preparing a simpler, low-cost brake test rig and provided an alternative way to obtain model physical parameter values.